TREATMENT OF LOW– AND INTERMEDIATE– LEVEL RADIOACTIVE LIQUID WASTE FROM ALTWATHA SITE USING IRAQI ZEOLITE (Journal of Engineering, 2007)
Ion exchange material used in this study is synthetic inorganic resin. It is Iraqi synthetic zeolite type Na-A, which was prepared from Iraqi kaolinite. The prepared zeolite pellets were solidified by heat treatment at 600oC for 3 hours. Nine radiochemical experiments were carried out on real (radioactive) samples. Five of these experiments were to study the uptake rate (sorption rate) of cobalt-60. The measured value for equilibrium time was one hour. The other experiments were carried out to obtain sorption isotherm using batch test. The product cobalt concentration was fitted to Langmuir and Freundlich isotherms as followed respectively:x/m= 1.25 Ce / (1+6*104 Ce)x/m= 8*10-4 Ce 0.4Gamma spectrometry analysis system of Sodium Iodide (NaI) detector coupled with a multichannel analyzer, was used for the measurements of radioactivity of the samples pre- and after treatment with zeolite. In general the experimental results have shown an efficient performance of the Iraqi zeolite to remove different cobalt concentration from low- and intermediate- level radioactive liquid waste.